2005
DOI: 10.1074/jbc.m505670200
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Location of a Conserved GTPase-associated Center of the Ribosome Induced by Mutagenesis Influences the Structure of Peptidyltransferase Center and Activity of Elongation Factor G

Abstract: Translocation catalyzed by elongation factor G occurs after the peptidyltransferase reaction on the large ribosomal subunit. Deacylated tRNA in the P-site stimulates multiple turnover GTPase activity of EF-G. We suggest that the allosteric signal from the peptidyltransferase center that activates EF-G may involve the alteration in the conformation of elongation factor binding center of the ribosome. The latter consists of the moveable GTPase-associated center and the sarcin-ricin loop that keeps its position o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…The base reactivity changes we observe in the DSRL 50S subunits show extensive overlap with those in a previous study in which a G-C base pair was inserted at position 1030-1124, at the base of h42, which connects to the GAC (Sergiev et al 2005). This mutation was predicted to lengthen and rotate h42, moving the GAC to a ''downward'' position.…”
Section: Discussionsupporting
confidence: 52%
“…The base reactivity changes we observe in the DSRL 50S subunits show extensive overlap with those in a previous study in which a G-C base pair was inserted at position 1030-1124, at the base of h42, which connects to the GAC (Sergiev et al 2005). This mutation was predicted to lengthen and rotate h42, moving the GAC to a ''downward'' position.…”
Section: Discussionsupporting
confidence: 52%
“…Helix 89 Modifications in Presence of SBP2-Previous chemical probing studies have correlated a conformational change in the SRL with the selective binding of EF-G over EF-Tu in pretranslocation state ribosomes (17). Additionally, movement of the GAC has also been implicated in EF binding specificity (18). In our analysis, there were no differences in the reactivity of residues in the GAC or the SRL in the presence of SBP2 (data not shown).…”
Section: Resultsmentioning
confidence: 42%
“…occupancy status of the peptidyl-transferase center is allosterically transmitted to the factor-binding site, consisting of the GTPase-associated center and the sarcin/ricin loop. For example, structural probing experiments revealed a defined chain of nucleotides connecting the P-loop of the 23S rRNA to the elongation factor binding site, supporting the hypothesis that the occupancy status of the P-site determines the conformation of the movable GTPaseassociated center relative to the sarcin/ricin loop, to either enhance or inhibit EF-G binding (Sergiev et al 2005). In addition, extensive mutational analysis of the ribosomal protein L3 indicated that amino acid changes displaying the more pronounced mutant phenotypes were those in close proximity to functional regions of the 25S, the peptidyltransferase A-site and the sarcin/ricin loop.…”
Section: Discussionmentioning
confidence: 96%
“…This observation is relevant to the in vivo effects of PAP, given that eukaryotic cells contain excess amounts of eEF1A relative to eEF-2 and that eEF1A is not a limiting factor for protein synthesis (Slobin 1980). Recent structural analysis of the ribosome also showed that change in position of the GTPase-associated center relative to the sarcin/ricin loop altered the function of EF-G but not that of EF-Tu, suggesting that the structural requirements for activity of each elongation factor also differ (Sergiev et al 2005). Therefore, even though both factors bind the sarcin/ricin loop, the conformation of the loop and its depurination status may have differing effects on each factor.…”
Section: Discussionmentioning
confidence: 99%